A bowling ball and a bag together cost $88. The ball costs three times as much as the bag. How much does each cost?
The answer is $22 and $66 respectively. The way to get that answer is as follows:
Let the ball be X and they bag be Y.
x + y = 88
x = 3y
Now we substitute the value for x in the second equation into the first.
3y + y = 88
4y = 88
y = 22
So that tells us the price of the bag is $22.
If the price of the ball is 3 times that of the bag, 22*3 = 66.
We can also see this is true because 66 + 22 = 88.
Let us assume that the cost of the ball =x
The cost of the bag= y
Then the cost for both is:
But the cost of the ball = 3 times the cost of the bag
==> x= 3y
Now substitute with x=3y
==> x+y= 88
==> 3y+y= 88
==> 4y= 88
==> y= 88/4= 22
==> x= 3y= 3(22)= 66
Then the cost of the ball (x) = $66
and the cost for the bag (y)= $22
The condition that ball costs 3 times as much as the bag enables us to say ball costs 3x and the bag costs x. So the total cost is 3x+x = 4x which is actually $88. So the required equation is 4x = $88. Solving for x we get the cost of the bag. Therefore,
4x/4 = $88/4
x = $22, being the cost of bag.
Cost of the ball =3x = 3*$22 = $66.
There are two variable factors in this equation
let b= bowling ball price
let g= bag price
therefore, your system of equations is
you now can input 3g for b and your system of equations is now
now, simplify and solve your equation
now, substitute g in the previous equation b+g=88
The bowling ball costs 66 dollars and the bag costs 22 dollars
Hope this helps!
Use the first link for free solutions, check it out to see if your book is included
let the cost of bag=x
Cost of ball=3*(Cost of bag)=3x
Cost of bag=x=$22
coat of ball=3*x=3*$22=$66
the cost of a bowling ball be x.
the cost of a bag be y.
then ACCORDING TO THE STATEMENT, we will get the following eqn
x + y =88[eqn 1]
now,the question says that ball costs 3 times as much as bag.
which implies that, x = 3y[eqn 2]
now by using the elimination method,
x + y =88
x = 3y which implies that x-3y=0
now multiplying eqn 1 by 3,we get
subtracting these two eqns, we get
which implies that, x=264/4
therefore cost of ball=x =66
cost of bag=y=22.